A REVIEW ON ARTIFICIAL BLOOD: A SOURCE WE NEED - R, Krishna Veni; P, Brindha Devi; S, Ivo Romauld (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Blood is a liquid tissue, in which abundant chemical factors and millions of different cells are dissolved. It is one of the most demanding sources in clinical and medical aspects. The issues and cost of human blood collection and storage directed this procedure toward the use of alternative blood. Thus, came an invention of artificial blood and blood substitutes. These alternative blood or blood substitute is a substance which is made to play as a substitute of erythrocytes. Thus, the main objective is to replace the normal human blood with artificial blood substitutes in the place of blood transfusion during surgeries and organ transfusion. Two major and focused blood substitutes in pharmaceutical aspects are perfluorocarbons and hemoglobin-based oxygen carriers (HBOC's). Among these HBOCs vaguely resemble normal human blood. These blood substitutes are to allow flow through the blood stream to carry the oxygen and supply it to heart and other parts of the blood. They are used to fill the lost fluid volume. They are also called as plastic blood with iron atom as the base. They are found to serve as a good oxygen carrier. The results showed by these products are discussed, and they proved that they can act as a blood substitute and also they can reach the human tissue easier than erythrocytes and can control oxygen directly. However, these artificial blood products are being processed in research laboratories for good outcome. Their important functions are oxygen carrying capacity and to replace the lost blood volume in the human body. Their special features are survivability over a wider range of temperatures, eliminating cross matching, cost efficient, pathogen free, long shelf life, minimal side effects. Thus, artificial blood products are really a good alternative source which we need for replacing normal human blood.